Audacious Education Purposes How Governments Transform the Goals of Education Systems - Reimers, Fernando M. (Springer Nature, 2020)
This open access book offers a comparative study of eight ambitious national reforms that sought to create opportunities for students to gain the necessary breath of skills to thrive in a rapidly changing world. It examines how national governments transform education systems to provide students opportunities to develop such skills. It analyses comprehensive education reforms in Brazil, Finland, Japan, Mexico, Peru, Poland, Portugal and Russia and yields original and important insights on the process of educational change. The analysis of these 21st century skills reforms shows that reformers followed approaches which are based on the five perspectives: cultural, psychological, professional, institutional and political. Most reforms relied on institutional and political perspectives. They highlight the systemic nature of the process of educational change, and the need for alignment and coherence among the various elements of the system in order. They underscore the importance of addressing the interests of various stakeholders of the education system in obtaining the necessary impetus to initiate and sustain change. In contrast, as the book shows, the use of a cultural and psychological frame proved rarer, missing important opportunities to draw on systematic analysis of emerging demands for schools and on cognitive science to inform the changes in the organization of instruction. Drawing on a rich array of sources and evidence the book provides a careful account of how education reform works in practice.